Taxonomic revision of the species of Parvanachis Radwin, 1968 (Gastropoda: Columbellidae) from the Gulf of Panama - de Maintenon, Marta J. (Zootaxa, 2014)
Species of Parvanachis Radwin, 1968 collected from the Gulf of Panama are anatomically characterized and taxonomically revised. Six species are reported to occur in the region: P. pygmaea (Sowerby, 1832), P. pardalis (Hinds, 1843), P. diminuta (C.B. Adams, 1852), P. albonodosa (Carpenter, 1857), P. milium (Dall, 1916), and P. dalli Bartsch, 1931. Of these six, three are confirmed as described. P. milium was not found in new collections or the previous survey collection and may be more common further south. P. dalli is a synonym of P. pygmaea; and P. albonodosa (auct.) is renamed, because the type material represents a different species. Two new species are described, P. dichroma and P. adamsi. P. pardalis, based on anatomy and shell and radular morphology, is referred to the genus Anachis, and Costoanachis nigricans (Sowerby, 1844), based on anatomy and shell morphology, is transferred to Parvanachis. The resulting seven species of Parvanachis constitute two groups; one (including the type species) with smaller shells and a simple penis morphology, and a group of four larger species with more complex penis morphology.